The Synthesis of New Type II Polymeric Photoinitiator (thioxantone) via Atom Transfer Radical Polymerization and Their Curing and Migration Studies - GENÇOĞLU, EFE NEJAT; ARMAN KANDIRMAZ, EMİNE; KAYAMAN APOHAN, NİLHAN (POLYMER SOC KOREA, 2019)
Polymeric photoinitiators are widely used in ultraviolet (UV)-curable printing inks because of their low migration behavior. In this study, a new phenylphosphine oxide-polystyrene-thioxanthone (PPO-PSt-TX) polymeric photoinitiator was synthesized. Bis[(4-hydroxy)phenyl]phenyl phosphine oxide (BHPPO) that was synthesized by Grignard technique, was functionalized with 2-bromopropionyl bromide (atom transfer radical polymerization (ATRP) initiator) and then used in styrene polymerization. The bromine end-capped polystyrene was then reacted with 2-thioxanthone-thioacetic acid and final polymeric photoinitiator PPO-PSt-TX was obtained. Proton nuclear magnetic resonance (1H NMR), attenuated total reflectance- Fourier transform infrared spectroscopy (ATR-FTIR), gel permeation chromatography (GPC) and ultraviolet-visible spectroscopy (UV-Vis) confirmed the obtained structure. The curing characteristic of PPO-PSt-TX was compared with a standard flexographic printing varnish formulation containing thioxanthone (TX). The photopolymerization kinetics were determined by photo differential scanning calorimetry (Photo-DSC). The conversion of methylmethacrylate polymerization by using macrophotoinitiator is 78%. The migration behavior of PPO-PSt-TX was identified with liquid chromatography-mass spectrometry (LC-MS). It was shown that PPOPSt- TX macro photoinitiator is suitable for flexographic varnish and the migration level of photoinitiator is reduced by using polymeric photoinitiator.
Keywords: polymeric photoinitiator; photopolymerization; thioxanthone; migration; flexographic varnish; IN-CHAIN THIOXANTHONE; FOOD-PACKAGING MATERIALS; AMINE; MACROPHOTOINITIATOR; ACID